"Not the 'Grim Reaper Service'": An Assessment of Provider Knowledge, Attitudes, and Perceptions Regarding Palliative Care Referral Barriers in Heart Failure. Issue 1 (2nd January 2014) - Kavalieratos, Dio; Mitchell, Emma M.; Carey, Timothy S.; Dev, Sandesh; Biddle, Andrea K.; Reeve, Bryce B.; Abernethy, Amy P.; Weinberger, Morris
Abstract : Background: Although similar to cancer patients regarding symptom burden and prognosis, patients with heart failure (HF) tend to receive palliative care far less frequently. We sought to explore factors perceived by cardiology, primary care, and palliative care providers to impede palliative care referral for HF patients. Methods and Results: We conducted semistructured interviews regarding (1) perceived needs of patients with advanced HF; (2) knowledge, attitudes, and experiences with specialist palliative care; (3) perceived indications for and optimal timing of palliative care referral in HF; and (4) perceived barriers to palliative care referral. Two investigators analyzed data using template analysis, a qualitative technique. We interviewed 18 physician, nurse practitioner, and physician assistant providers from 3 specialties: cardiology, primary care, and palliative care. Providers had limited knowledge regarding what palliative care is, and how it can complement traditional HF therapy to decrease HF‐related suffering. Interviews identified several potential barriers: the unpredictable course of HF; lack of clear referral triggers across the HF trajectory; and ambiguity regarding what differentiates standard HF therapy from palliative care. Nevertheless, providers expressed interest for integrating palliative care into traditional HF care, but were unsure of how to initiate collaboration. Conclusions: Palliative care referral for HF patients may be suboptimal due to limited provider knowledge and misperceptions of palliative care as a service reserved for those near death. These factors represent potentially modifiable targets for provider education, which may help to improve palliative care referral for HF patients with unresolved disease‐related burden.